2009
DOI: 10.1111/j.1365-2125.2009.03456.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessing analgesic actions of opioids by experimental pain models in healthy volunteers – an updated review

Abstract: AIMExperimental pain models may help to evaluate the mechanisms of action of analgesics and target the clinical indications for their use. This review addresses how the efficacy of opioids can be assessed in human volunteers using experimental pain models. The drawback with the different study designs is also discussed. METHODA literature search was completed for randomized controlled studies which included human experimental pain models, healthy volunteers and opioids. RESULTSOpioids with a strong affinity fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
134
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(137 citation statements)
references
References 130 publications
(301 reference statements)
2
134
0
1
Order By: Relevance
“…These pain assays measure different aspects of pain processing, with pressure stimuli involving sensitivity of deep tissue afferents and thermal stimuli involving C-fiber hyperexcitability (especially temporal summation). 5,50,51 This is not a new finding, as there is low to moderate correlation across different pain stimuli when examined on the same individual. 34,36 However, this is important to recognize, as many prior studies 15,17,18,[20][21][22]31 that have reported on side-to-side comparisons utilized only a single type of stimulus.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…These pain assays measure different aspects of pain processing, with pressure stimuli involving sensitivity of deep tissue afferents and thermal stimuli involving C-fiber hyperexcitability (especially temporal summation). 5,50,51 This is not a new finding, as there is low to moderate correlation across different pain stimuli when examined on the same individual. 34,36 However, this is important to recognize, as many prior studies 15,17,18,[20][21][22]31 that have reported on side-to-side comparisons utilized only a single type of stimulus.…”
mentioning
confidence: 90%
“…Such use of pressure stimuli is also supported by the association between local PPT and clinical pain intensity. Palpation is the clinical correlate of pressure algometry 50 and may be useful as a measure of pain response, especially to provoke pain in specific regions of muscles. 3,4,26 Furthermore, it may be possible to distinguish between altered peripheral and central pain processes with the application of pressure stimuli.…”
mentioning
confidence: 99%
“…As the physiology of deep and superficial pain differs, the results will furthermore be divided into the tissue (skin, muscle or viscera) in where the pain was induced, and into modalities used for pain stimulation. For a more thorough introduction to human experimental pain models, see the first review in this series involving opioid analgesics [5].…”
Section: Introductionmentioning
confidence: 99%
“…Future studies are needed to help establish whether pain hypersensitivity in PD extends to suprathreshold levels of pain, and insights may also be gained from the use of ischemic and dermal capsaicin experimental pain models that evoke several aspects of chronic pain whilst preserving strict experimental control [50]. More research involving preclinical models and neuroimaging techniques in humans would also help to elucidate potential mechanistic pathways underlying altered pain perception in PD.…”
Section: Future Research Directionsmentioning
confidence: 99%